Role of intellectual capital on organisational sustainability / Nur Hayati Ab Samad - Ab Samad, Nur Hayati (2015)
In order to successfully accomplish their social and business mission, social entrepreneurial non-profit organisations (NPOs), which are also known as social enterprises, need to identify the appropriate elements of resources that affect their performance, since the management of resources is important to ensure organisational sustainability in the future. Thus, this study aims to examine the role of intellectual capital, in terms of human capital (HC), structural capital (SC) and relational capital (RC) on the sustainability of social enterprise in Malaysia. Content analysis was used as the research instrument in order to measure the sustainability index from information disclosed in the annual reports by 210 organisations registered under the Registry of Societies (ROS) in Malaysia for the year 2010. Various statistical analyses were carried out to examine the relationship between IC and the sustainability of social enterprise. Based on the multivariate analysis, the results have highlighted that SC had significant positive influence on sustainability of social enterprise while HC and RC did not have a significant positive relationship with the sustainability of social enterprise. Overall, this study hopes to contribute to a better understanding on the role' of IC on the sustainability of social enterprise. The findings offered several main implications for academicians, researchers, regulators as well as for the social enterprise itself by highlighted that SC was the most influential factor that was able to increase the sustainability of the social enterprise.